2020
DOI: 10.2151/jmsj.2020-002
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, Physical Mechanisms, and Prediction of Pre-summer Rainfall over South China: Research Progress during 2008–2019

Abstract: Pre-summer rainy season (April to mid-June) over South China (SC) is characterized by high intensity and frequent occurrence of heavy rainfall in the East Asian monsoon region. This review describes recent progress in the research related to such a phenomenon. The mechanisms responsible for presummer rainfall consist of multi-scale processes. Sea surface temperatures over tropical Pacific and Indian Ocean are shown to have a great influence on the interannual variations of pre-summer rainfall over SC. Synoptic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
47
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 106 publications
2
47
0
Order By: Relevance
“…Efforts have also been made to develop numerical weather prediction (NWP) technique including data assimilation (Bao et al., 2017; Zhang et al., 2016), model physic parameterization (Furtado et al., 2018, 2020; Qian et al., 2018), and perturbation‐generation methods for ensemble forecast (Zhang 2018, 2019). Despite all these research progresses (summarized by Luo et al., 2020), it remains challenging to make timely and accurate forecast for the pre‐summer warm‐sector heavy rainfall over coastal SC under relatively weaker large‐scale dynamic lifting. Improving the forecast skill requires better understanding the processes governing the convection initiation (CI) of such coastal heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…Efforts have also been made to develop numerical weather prediction (NWP) technique including data assimilation (Bao et al., 2017; Zhang et al., 2016), model physic parameterization (Furtado et al., 2018, 2020; Qian et al., 2018), and perturbation‐generation methods for ensemble forecast (Zhang 2018, 2019). Despite all these research progresses (summarized by Luo et al., 2020), it remains challenging to make timely and accurate forecast for the pre‐summer warm‐sector heavy rainfall over coastal SC under relatively weaker large‐scale dynamic lifting. Improving the forecast skill requires better understanding the processes governing the convection initiation (CI) of such coastal heavy rainfall.…”
Section: Introductionmentioning
confidence: 99%
“…The coastal regions of South China witness the most active convection in China, especially after the onset of the East Asian summer monsoon (Luo et al, 2017(Luo et al, , 2020. The orographic effects and the convergence between land breezes/downslope winds and low-level onshore flows (especially the onshore marine LLJ) play an important role in the regional hydrologic cycle (Bao et al, 2021;Luo et al, 2020;Wang et al, 2021). The CI occurrences in this region are pronounced from June to August, with a primary peak in the early afternoon and a secondary peak at midnight (Bai et al, 2020a).…”
mentioning
confidence: 99%
“…The mean R in (Figure 2c) of pre‐summer rainfall increases from a minimum of 2.5 mm/hr after midnight to a maximum of 3.8–4.0 mm/hr in the morning (06–09 HKT), and then quickly declines until the night. This is associated with the enhanced transport of warm and moist air of tropical origin and the induced low‐level convergence during the onset of the East Asian summer monsoon (Luo et al., 2020). The mean R in of mid‐summer rainfall also increases after midnight to a peak of 3.8 mm/hr in early morning (09 HKT), however, nocturnal rainfall of mid‐summer is substantially stronger than that of pre‐summer, which explains the higher nocturnal R cu in mid‐summer (Figure 2a).…”
Section: Resultsmentioning
confidence: 99%
“…In this section, a further analysis of the possible contributors is presented to probe the possible mechanism behind this. Previous studies have demonstrated that the DCR in South China is due to multi‐scale conditions and in‐between interaction, the key factors include temperature, moisture availability, low‐level monsoonal flow, and land‐sea breeze (Chen et al., 2018; Luo et al., 2020). The variability of these factors and their correlations with the changes in rainfall over CSC during stage III* are examined based on the ERA5.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation